Role of nitric oxide of the median preoptic nucleus (MnPO) in the alterations of salivary flow, arterial pressure and heart rate induced by injection of pilocarpine into the MnPO and intraperitoneally - Saad, Wilson A. [UNESP]; Guarda, I.F.M.S.; Camargo, L.A.A. [UNESP]; Santos, T.A.F.B.; Guarda, R.S.; Saad, Willian A.; Simões, S.; Antunes Rodrigues, J. (Associação Brasileira de Divulgação Científica (ABRADIC), 2003)
We investigated the effect of L-NAME, a nitric oxide (NO) inhibitor and sodium nitroprusside (SNP), an NO-donating agent, on pilocarpine-induced alterations in salivary flow, mean arterial blood pressure (MAP) and heart rate (HR) in rats. Male Holtzman rats (250-300 g) were implanted with a stainless steel cannula directly into the median preoptic nucleus (MnPO). Pilocarpine (10, 20, 40, 80, 160 µg) injected into the MnPO induced an increase in salivary secretion (P<0.01). Pilocarpine (1, 2, 4, 8, 16 mg/kg) ip also increased salivary secretion (P<0.01). Injection of L-NAME (40 µg) into the MnPO prior to pilocarpine (10, 20, 40, 80, 160 µg) injected into the MnPO or ip (1, 2, 4, 8, 16 mg/kg) increased salivary secretion (P<0.01). SNP (30 µg) injected into the MnPO or ip prior to pilocarpine attenuated salivary secretion (P<0.01). Pilocarpine (40 µg) injection into the MnPO increased MAP and decreased HR (P<0.01). Pilocarpine (4 mg/kg body weight) ip produced a decrease in MAP and an increase in HR (P<0.01). Injection of L-NAME (40 µg) into the MnPO prior to pilocarpine potentiated the increase in MAP and reduced HR (P<0.01). SNP (30 µg) injected into the MnPO prior to pilocarpine attenuated (100%) the effect of pilocarpine on MAP, with no effect on HR. Administration of L-NAME (40 µg) into the MnPO potentiated the effect of pilocarpine injected ip. SNP (30 µg) injected into the MnPO attenuated the effect of ip pilocarpine on MAP and HR. The present study suggests that in the rat MnPO 1) NO is important for the effects of pilocarpine on salivary flow, and 2) pilocarpine interferes with blood pressure and HR (side effects of pilocarpine), that is attenuated by NO.
Keywords: Pilocarpine; Nitric oxide; Central nervous system; Salivation; Arterial pressure; Heart rate